2011
DOI: 10.1111/j.1471-4159.2011.07376.x
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine attenuates levodopa‐induced dyskinesia in mice and rats preventing the accompanying rise in nigral GABA levels

Abstract: J. Neurochem. (2011) 118, 1043–1055. Abstract Amantadine is the only drug marketed for treating levodopa‐induced dyskinesia. However, its impact on basal ganglia circuitry in the dyskinetic brain, particularly on the activity of striatofugal pathways, has not been evaluated. We therefore used dual probe microdialysis to investigate the effect of amantadine on behavioral and neurochemical changes in the globus pallidus and substantia nigra reticulata of 6‐hydroxydopamine hemi‐lesioned dyskinetic mice and rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 83 publications
4
59
1
Order By: Relevance
“…Co-treatment salinelevodopa, or amantadine-levodopa was performed daily for three days, and the differences between groups in the severity of dyskinesia were assessed after the last daily injection of levodopa + carbidopa. In agreement with previous reports (Bido et al, 2011), dyskinetic animals pretreated with amantadine showed attenuated severity of all types of dyskinesias, reduced by about 60% along the time course after levodopa injection compared with dyskinetic animals pretreated with saline, demonstrating highly significant differences between the two groups ( Fig. 1a, b).…”
Section: Levodopa Induced Dyskinesias and Preventive Effect Of Amantasupporting
confidence: 93%
See 2 more Smart Citations
“…Co-treatment salinelevodopa, or amantadine-levodopa was performed daily for three days, and the differences between groups in the severity of dyskinesia were assessed after the last daily injection of levodopa + carbidopa. In agreement with previous reports (Bido et al, 2011), dyskinetic animals pretreated with amantadine showed attenuated severity of all types of dyskinesias, reduced by about 60% along the time course after levodopa injection compared with dyskinetic animals pretreated with saline, demonstrating highly significant differences between the two groups ( Fig. 1a, b).…”
Section: Levodopa Induced Dyskinesias and Preventive Effect Of Amantasupporting
confidence: 93%
“…or subcutaneously 1 h before (Antonioli et al, 2007); PDE2 inhibitor BAY60-7550 by gavage 3 mg/kg 30 min before (van Donkelaar et al, 2008); PDE10A inhibitor papaverine 3 mg/kg i.p. 20 min before (such low dose of papaverine was chosen because it can inhibit phencyclidinestimulated locomotor activity avoiding inhibition of spontaneous locomotor activity; Siuciak et al, 2006); PDE1A inhibitor and NMDA receptor antagonist amantadine 40 mg/kg s.c. 1 h before (Bido et al, 2011;Kakkar et al, 1997). Moreover, to test the specific antidyskinetic effect of amantadine we used also memantine, dimethyl derivative of amantadine, known only as NMDA receptor antagonist (2 mg/kg s.c. 1 h before) (Beconi et al, 2011).…”
Section: Treatment With Amantadine and Selective Pde Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of a selective Fyn antagonist is desirable. Mice responding to saracatinib show a reduction of LID scores and FosB/∆FosB staining in the order of 30% compared to controls, which is comparable to what has been reported with other drugs that have previously shown efficacy against LID in the same animal model, such as amantadine or riluzole [6,28]. We may conclude that, in agreement with our findings in Fyn-KO mice, there seems to be a plateau of therapeutic effect with every drug that has been tested, giving further support to the hypothesis that several mechanisms are involved in the development of LID.…”
Section: Discussionsupporting
confidence: 84%
“…In this scenario, the greatest clinical challenge is to reduce the development of LID without affecting the positive restorative effect of DA stimulation, and the NMDAR is a desired target to achieve such a goal as amantadine alleviates LID by reducing glutamate signaling [6], without affecting DA response [5,7]. In addition to the classical signaling downstream of the dopamine receptors, which likely participate in both the therapeutic and side effects of dopamine stimulation, the postsynaptic density (PSD) zone is determinant of plastic rearrangements and a candidate area aiming at dissecting both effects.…”
Section: Introductionmentioning
confidence: 99%